Características demográficas nutricionales y anemia en niños menores de 5 años puesto de Salud I – 1 Santa María del Ojeal Iquitos 2024 - Chavez Medina, Wilmer (2024)
The main objective was to determine the relationship between demographic and nutritional characteristics with anemia in children under 5 years old at Health Post I-1 Santa María del Ojeal, Iquitos 2024. The research was quantitative, non-experimental, descriptive, cross-sectional, and correlational. The sample consisted of 95 children under 5 years old who attended growth and development consultations at Health Post I-1 Santa María del Ojeal, Iquitos. The technique used was an interview, and the instrument was a data collection form for demographic, nutritional characteristics, and identifying the level of anemia in children under 5 years old. Data processing was carried out using the SPSS statistical software version 27.0, and the chi-square test (χ²) was used for correlation analysis. The results regarding demographic characteristics showed that 41.1% were preschoolers and 52.6% were female. Regarding nutritional characteristics, 68.5% had normal weight, 18.9% were underweight, and 12.6% were overweight. Regarding feeding type, 83.2% had inadequate nutrition for their age, and only 16.8% had adequate nutrition for their age. Regarding anemia, 55.8% did not have anemia, 30.5% had mild anemia, and 13.7% had moderate anemia. Conclusion: A statistically significant relationship was found between age (p = 0.010), sex (p = 0.001), nutritional status (p = 0.004), type of diet (p = 0.017), and anemia in children under 5 years old.